Ecologies of Practice in Musical Performance - Harlow, Randall (MUSICultures, 2019)
This article presents an ecological model of musical performance drawn from the field of Gibsonian Ecological Psychology and the techniques of Actor-Network Theory as explicated by Bruno Latour and others. Citing a wide body of empirical research, it is argued that musicians and their musical instruments exist in an ecological relationship at the level of embodied gesture. Furthermore, it is proposed that every act of musicking amounts to a construction of a network of actors that define an “Ecology of Practice,” a thick description more fully encompassing the complexities of musicking than traditional notions of performance practice.